SIFAT FISIK DAN MEKANIK PAPAN PARTIKEL DARI AMPAS JARAK KEPYAR - Mersi Kurniati, Ika Amalia Kartika, Farah Fahma, Titi Candra Sunarti, Kaswar Syamsu, Dede Hermawan T (Jurnal Teknologi Industri Pertanian, 2014)
ABSTRAK   The castor cake meal was a by-product of castor oil production and its has recently been highly rated as a source of raw material for particle board, because beyond its high protein content (32-48%)  and fibre (28-33%). The objective of this research was to produce and investigate the physical and mechanical properties of the particle board from castor cake meal. Particle board samples were manufactured using hot pressing temperatures (150-1900C), pressing time (4-12 minutes), compressed using a pressure  (140-220 kg/cm2) with  particles size of 20-100 mesh. The central composite design (CCD) method and ANOVA (α=0.05) with  response surface method (RSM) were used to evaluate production of the particle board. The physical and mechanical properties of particle board  were determined based on Japanese Industrial Standards, JIS A 5908-2003 type-8. The experimental results showed that the pressing process conditions affected the physical and mechanical properties of particle board. The particle size were significant factor for moisture content, density, water absorption and thickness swelling, pressing temperature were significant factors for modulus of elasticity,modulus of rupture and internal bonding of particle board. The smaller particle size (20 to 60 mesh) and the higher pressing temperature (150 to 1700C), increased moisture content, density, modulus of elasticity, modulus of rupture,  and bonding strength and decreased water absorption  and thickness swelling of particle board. Physical and mechanical properties obtained from the best process conditions at a temperature of 1700C, time of 8 minutes, pressure of 180 kgf/cm2 and 60 mesh particle size. Based on the overall results, the physical and mechanical properties of particle board did not met requirement of the JIS A 5908-2003 except for moisture content, density and internal bonding. Keywords: castor cake meal, particle board, modulus of elasticity,modulus of rupture, internal bonding